Does size matter?: Center-specific characteristics and survival after allogeneic hematopoietic cell transplantation for acute myeloid leukemia: an analysis of the German Registry for Stem Cell Transplantation and Cell Therapy : acute myeloid leukemia - Bethge, Wolfgang Andreas; Flossdorf, Sarah; Hanke, Franziska; Schmid, Christoph; Ringhoffer, Mark; Klein, Stefan; Hertenstein, Bernd; Schetelig, Johannes; Stelljes, Matthias; Schroeder, Thomas; Blau, Igor Wolfgang; Ayuk, Francis; et al. (Haematologica, 2025)
We investigated the effect of center-specific variables on overall survival (OS) after allogeneic hematopoietic cell transplantation (alloHCT) in acute myeloid leukemia (AML). Eligible for the study were adult patients reported to the German Registry for Hematopoietic Stem Cell Transplantation and Cell Therapy (DRST) receiving first alloHCT for AML from a related or matched (>9/10 HLA-match) unrelated donor in the period 2015-2021. Primary endpoint was OS at 12 months from alloHCT. Univariable and multivariable analyses after best subset selection were performed. Of 5,328 patients, 83% received alloHCT in a high-volume center (≥40 alloHCT/year), 90% in a university hospital, 90% in a center performing alloHCT for ≥10 years, and 73% in a Joint Accreditation Committee ISCT-Europe & European Group for Blood and Marrow Transplantation (EBMT) (JACIE) accredited center. 52% of the patients were in first CR, and European LeukemiaNet risk was adverse in 37% and intermediate in 42%. On multivariable analysis, center-specific factors predicting adverse 12-month OS were program duration <5-10 years (Hazard Ratio [HR] 1.23, [95% Confidence Interval: [1.02; 1.49]), center volume <40 alloHCT/year (HR 1.21, [1.02; 1.45]), and treatment at a non-university hospital (HR 1.21, [0.98; 1.49]), whereas JACIE accreditation did not. Spline modeling suggested a negative effect of a center volume up to 45 alloHCT per year. Center volume, center experience, university hospital, but not JACIE accreditation, have an impact on alloHCT outcomes in adult patients with AML in Germany.
Gesehen am 25.09.2025